Impact of Consumer Motivation and Behavior on Social Instagram Media Platforms Somethinc Skincare Purchases - Natalia, Ros; Sutawidjaya, Ahmad Hidayat (Jurnal Ilmiah Manajemen Kesatuan, 2024)
In the current digital era, sosial media has become a highly influential platform in the consumer decision-making process, especially in the beauty industry. Instagram, as one of the leading sosial media platforms, plays a significant role in shaping consumer preferences and behaviors related to skincare products. This study aims to examine the impact of consumer motivation and behavior on the purchase of Somethinc skincare products on the Instagram sosial media platform. This research employs a quantitative approach with an explanatory method. The sampling technique used is Non-Probability Sampling with Purposive Sampling, involving a sample size of 100 individuals. The results of the study indicate that intrinsic motivation has a positive influence on purchase decisions, extrinsic motivation also has a positive influence on purchase decisions, and knowledge about the product positively and significantly affects the purchase of Somethinc skincare. However, the attitude toward the product does not have a positive and significant impact on the purchase of Somethinc skincare. Keywords: Motivation, Consumer Behavior, Purchase, Instagram Sosial Media Platform.